2013
DOI: 10.2147/opth.s47448
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein occlusion during flare of multicentric Castleman's disease

Abstract: We report a case of successive bilateral retinal vein occlusion in a human immunodeficiency virus (HIV)-positive male with multicentric Castleman’s disease treated successfully with a single injection of intravitreal bevacizumab. Castleman’s disease should be a differential diagnosis of occlusive retinovascular disease and, occasionally, ocular manifestation can lead to systemic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“… 9 Less frequently reported ocular signs are retinal hemorrhage, subretinal fluid, macular edema, cotton wool spot, choroidal neovascularization, central retinal artery occlusion, and serous retinal detachment. 10 , 11 The ocular findings of bilateral optic disc swelling with macula edema seen as a coinfection with B. henselae neuroretinitis as highlighted in our case has not been presented in any previous review.…”
Section: Discussionmentioning
confidence: 65%
“… 9 Less frequently reported ocular signs are retinal hemorrhage, subretinal fluid, macular edema, cotton wool spot, choroidal neovascularization, central retinal artery occlusion, and serous retinal detachment. 10 , 11 The ocular findings of bilateral optic disc swelling with macula edema seen as a coinfection with B. henselae neuroretinitis as highlighted in our case has not been presented in any previous review.…”
Section: Discussionmentioning
confidence: 65%
“…CD rarely leads to direct involvement of the orbit or ocular structures due to a lack of lymphoid tissue in the eye [10]. Several investigators have reported rare intraocular involvement [7][8][9][10][11][12]; however, the pathogenic mechanism of ocular involvement is not fully understood. We report a case of hypertensive choroidopathy in a patient with CD associated with malignant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to optic disk edema, Roth's spot was observed in the present case on fundus examination. Roth's spot can be observed in a variety of diseases but is rarely observed in patients with MCD [31], and it could be one of the ophthalmological manifestations of TAFRO syndrome.…”
Section: Discussionmentioning
confidence: 99%